Intangible capital and growth in advanced economies: Measurement methods and comparative results - Carol Corrado; Jonathan Haskel; Cecilia Jona-Lasinio; Massimiliano Iommi (Institute for the Study of Labor (IZA), 2012)
We present a harmonized data set on intangible investment for a number of EU countries and an analysis of growth.
Keywords: O47; 330; growth; intangible investment; Immaterielles Anlagevermögen; Wirtschaftswachstum; Schätzung; EU-Staaten